15.3% efficient graded bandgap solar cells fabricated using electroplated CdS and CdTe thin films. (15th October 2016) - Ojo, A.A.; Dharmadasa, I.M.
Highlights: Use of all electroplated materials from 2-electrode system to fabricate PV structures. Fabrication of n-n-p, three layer devices using unambiguously semiconductor material. Production of 15.3% efficient solar cell from multilayer graded bandgap configuration. Abstract: Making use of previously designed and experimentally tested results of graded bandgap devices, and the comprehensive electrodeposition of semiconducting materials knowledge, a three layer n-n-p device structure was fabricated and tested for their electronic properties and solar cell performance. Glass/FTO/n-CdS/n-CdTe/p-CdTe/Au devices were fabricated and studied as a first step towards development of graded bandgap devices using electroplated materials. Efficiencies up to 15.3% were observed for lab-scale small devices.